2005
DOI: 10.1103/physrevlett.94.087401
|View full text |Cite
|
Sign up to set email alerts
|

Optical Polarization Driven Giant Relief Modulation in Amorphous Chalcogenide Glasses

Abstract: We report on the observation of giant relief modulation in amorphous chalcogenide As2S3 glass under polarization modulated near band gap light illumination. We show that these periodic modulations are created as a result of the photoinduced mass transport despite the very low and uniform intensity light illumination. A phenomenological model, based on a photoinduced alignment of anisotropic microvolumes within the glass, is proposed to explain the phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…In addition, above bandgap irradiation is associated with high absorption that is sufficient to induce a significant warming and even potential damage, while sub-bandgap irradiation has a negligible thermal contribution under standard irradiation power. Several proofs of the optical origin and athermal nature of photoinduced effects exist including the fact that photofluidity is more pronounced at low temperature [10] and exhibits polarization effects [19] or the formation of wavelength specific Bragg gratings [20]. Nevertheless, it has been recently suggested that the thermal contribution to the photoexpansion itself may not be negligible even for weakly absorbed light [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, above bandgap irradiation is associated with high absorption that is sufficient to induce a significant warming and even potential damage, while sub-bandgap irradiation has a negligible thermal contribution under standard irradiation power. Several proofs of the optical origin and athermal nature of photoinduced effects exist including the fact that photofluidity is more pronounced at low temperature [10] and exhibits polarization effects [19] or the formation of wavelength specific Bragg gratings [20]. Nevertheless, it has been recently suggested that the thermal contribution to the photoexpansion itself may not be negligible even for weakly absorbed light [21].…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of the mass transfer is very sensitive to the light po-58 larization and intensity [9][10][11][12].…”
mentioning
confidence: 99%
“…In the previous studies, 16,22,23,25 As 2 S 3 films were deposited onto microscope slides, which were exposed to focused linearly polarized laser beams. It was demonstrated that an isotropic expansion appears at first, which gradually transforms to an anisotropic M-shaped deformation with exposure time.…”
Section: A Anisotropic Deformationmentioning
confidence: 99%
“…21 The other is a photoinduced anisotropic M-shaped deformation in As 2 S 3 films. 16,22,23 Both of these phenomena are induced by illumination of linearly polarized band gap light. On the other hand, the OM effect appears only during illumination, i.e., it is transitory, while the anisotropic deformation exists in quasistable after illumination.…”
Section: Introductionmentioning
confidence: 99%